The rise of monogamy - Sadettin Haluk Citci (SERIEs - Journal of the Spanish Economic Association, 2014)
Why has polygyny, marriage of a man to multiple women, common in most societies throughout history, almost disappeared in modern industrialized countries? Do women play a role in its disappearance? A simple theoretical model suggests that at the later stage of the transition from polygyny to monogamy, the spread of human capital and the increase of labor income have led to the rise of monogamy. A general equilibrium model of the marriage market illustrates that the spread of human capital results in an increase in women's income opportunities and lowers the importance of bequests in determining their sons' incomes. Both effects improve women's outside option, mating monogamously, and decrease the marginal benefit of the economic advantages provided by polygynous unions. This, in turn, reduces polygyny by increasing the cost of polygynous mating for men. When the human capital level is sufficiently high, men find it optimal to marry monogamously instead of bearing the high cost of polygynous mating.
Keywords: J12; J24; O10; O40; Z13; 330; Marriage; Polygyny; Monogamy; Development; Human capital